The Effect of Quercetin on the Prevention and Treatment of Gynecologic Cancer - Arezou Biyabani; Afrooz Mazidimoradi; Fereshte Ghorbani; Leila Allahqoli; Hamid Salehiniya (Clinical and Experimental Obstetrics & Gynecology)
Objective: This review summarizes the molecular properties, anticancer effects, and bioavailability of quercetin (Que). We discussed its role in preventing and treating gynecologic cancers, assisting in the treatment of drug-resistant cases, and synergizing with other treatments. This review includes an analysis of Que’s impact on breast, ovarian, and cervical cancer. Mechanism: Gynecologic cancers are a significant cause of cancer-related deaths, leading to low survival rates and a high burden on patients and healthcare systems. They are regarded as a major health problem in women. The use of complementary therapies, such as Que, can contribute to improving patient outcomes and the quality of life. The utilization of medicinal plants as complementary and alternative medicine (CAM) is on the rise worldwide, offering new approaches to cancer treatment. This approach may provide potential treatments for various cancers, including female cancers such as breast, ovarian, and cervical cancer, either alone or in combination with other medications. Findings in Brief: Among various natural compounds, Que is commonly used as an anti-cancer supplement due to its antioxidant and anti-inflammatory properties. Que is effective in preventing and treating female cancers in a dose- and time-dependent manner, as demonstrated by numerous in vitro and in vivo studies and experiments. However, more clinical studies are required to establish this flavonoid as a therapeutic agent or as part of a drug combination in humans. Conclusions: Que helps prevent and treat gynecological cancers, reduce drug resistance, and increase the effectiveness of chemical drugs and radiotherapy. It achieves this through its anti-inflammatory, pro-oxidative, anti-proliferative, induction of apoptosis, and cell cycle arrest mechanisms. However, more human studies are needed to accurately determine of the mechanisms of action and the extent of its effectiveness.